DOES EMPLOYEE SATISFACTION AFFECT ORGANIZATIONAL BEHAVIOR? - Zara Khan; Muhammad Sarmad; Sadia Razzaq; Iqra Gulzar; Adeel Ahmad (Malaysian E Commerce Journal, 2020)
The main purpose of study is that how the employee satisfaction is effected in an organization. In this paper we also study that which type of factors effect organizational behavior and employee satisfaction in an organization, either in a positive or a negative way. The total number of one hundred and twenty (120) respondents was selected from different organizations which are working on the development sector. The respondents or the employees who were considered are managers, staff members, professionals and senior managers. SPSS 20.0 version was used for analysis. This study shows the extensive impact of job satisfaction on organizational performance in different organizations. The findings of this study show that the factors like reward system, promotions, bonuses and increase in salary are playing an important role to satisfy, attract and retain the employees. We also find that the senior employees are more satisfied than the employees who are less experienced. The research limitation of this study is that our research is consisting of a specific area. It characterizes the limited results. For the more accuracy of the results, we conduct this research on a large scale instead of some banks or organizations. This study is very helpful for the employees, organizations, industries, businessman, and banks. The employee satisfaction affects the organizational performance. The employee can be satisfied through reward systems, promotions, bonuses and increase in salaries. The employee’s satisfaction can increase the organizational performance. This research is 100% accurate because all the data is collected from Burewala-Vehari.